MOTHER WHO KILLS HER CHILDREN: A CASE REPORT - Achakzai, Abdul Malik; Kasi, Pashtoon Murtaza (Journal of Pakistan Psychiatric Society, 2007)
Puerperal psychosis is not uncommon in women passing through postnatal period, while neglect and harm to the baby is an important complication of this psychiatric disorder. We report a case, in which a mother in her postnatal period killed two children consecutively. The psychopathology, cultural beliefs and the legal aspects of this serious psychiatric problem are discussed. Key words: Postpartum Psychosis, Postpartum depression, Infanticide.